Joseph Needham in Korea, and Korea's Position in the History of East Asian Science. Issue 2 (1st June 2020) - Lim 林宗台, Jongtae
Abstract: As they were in other East Asian countries, Joseph Needham and his monumental works were warmly received by Korean historians of science in the late twentieth century. Korean historians appreciated both Needham's pioneering research on the history of Chinese science and his praise of Korea's contribution to East Asian scientific tradition, as expressed, for example, in the addenda to volume 3 of Science and Civilisation in China . But the Koreans' praise of Needham was not unqualified. Needham's largely favorable remarks on Korean science invited criticism from several prominent Korean historians who noted many factual errors, particularly relating to Korea's priority over China in several technological inventions. They regarded those errors as indicative of Needham's deep-rooted historiographical bias, his view of Korea as a mere tributary of China's scientific tradition. But the Koreans' criticism of Needham ironically shows that they agreed with the central tenets of Needham's methodology of crediting scientific achievements to different civilizations, whereby to measure China's contribution to what Needham termed "universal modern science." The Koreans only scaled down the scope of comparison from the world of civilizations to a smaller region called East Asia, whereby to compare Korea's share with that of China. This article thus takes the Korean criticism of Needham as an illuminating case, which invites us to think over a less explored issue in the history of East Asian science: how to write a balanced history of science in a region that is characterized by a stark disparity in power, resources, and achievements between China and its smaller neighbors.